Late Quaternary hydroclimate of the Levant: The leaf wax record from the Dead Sea. (1st August 2022) - Tierney, Jessica E.; Torfstein, Adi; Bhattacharya, Tripti
Abstract: The eastern Mediterranean is projected to experience increases in drought and extreme rainfall in response to rising greenhouse gas emissions. Paleoclimate records from this region are crucial to further constrain the response of the water cycle to a globally warmer climate. Of these, the Dead Sea lacustrine record, collected by the Dead Sea Deep Drilling Project (DSDDP), provides a detailed history of climate change over the past 200, 000 years and documents large-magnitude changes in regional water balance. Here, we analyze leaf wax isotopes ( δ D wax, δ 13 C wax ) on DSDDP 5017-1 and compare results to other proxies analyzed on the same core. The δ D wax record closely resembles the speleothem δ 18 O record from nearby Soreq Cave, suggesting that both record a regionally coherent signature of glacial-interglacial cycles and the interplay between winter season rainfall and large-scale expansion and contraction of the Afro-Asian monsoon system. Principal components analysis of the pollen and core lithology shows that the first-order driver of variability in the Dead Sea paleoclimate record is global temperature, which controls effective moisture by modulating atmospheric evaporative demand. Leaf wax, pollen, and core lithology all suggest radical changes in the annual cycle of precipitation during the peak of the Last Interglacial. We hypothesize that the Dead Sea Basin experienced a dual-rainfall regime during this time, with intensified winter storms and a summer monsoon season. While these changes were driven by the Earth's precessional cycle, model simulations suggest a similar expansion of the African monsoon domain into the Arabian Peninsula under elevated CO2 levels. The Last Interglacial climate of the DSB provides a glimpse of what future climate in the southeastern Mediterranean region could look like. Highlights: Leaf wax hydrogen and carbon isotope data from the Dead Sea are presented. Principal components analyses identifies modes of climate and landscape change. Multiple proxies highlight the role of temperature in driving Levant hydroclimate. Monsoon rains reached the Levant during the peak of the Last Interglacial.